Baru not surprised to be UUM lecturers new target - Borneo Post, (Kuching) (Borneo Post, 2017)
KUCHING: State Parti Keadilan Rakyat(PKR)chairman Baru Bian is not surprised that Universiti Utara Malaysia (UUM) lecturer Dr Kamarul Yusoff has started to target him.